Arthropod Abundance and Diversity in Pwadzu Dumpsite Wukari, Taraba State - Winifred, Ronald Abhulimen; Imbasi, Andokari Alheri (Darul Yasin Al Sys, 2024)
This study examined the Arthropod abundance and diversity in Pwadzu Dumpsite Wukari, Taraba State with coordinates 7.8847° N, 9.7717° E, the objectives of the study includes; Identification and distribution of Arthropods in Pwadzu Dumpsite in Wukari Local Government Area, evaluation of the abundance and distribution of the Arthropods using ecological indices of abundance and assessing the physical and chemical parameters of the soil in the dumpsite. Three sampling methods were used to collect arthropods from the different survey sites namely: water traps, sweep nets and handpicking with the aid of forceps and hand gloves. Arthropods collected from the survey site were recorded in order to study the relative abundance and distribution of the species found in the dumpsite. The arthropods were placed in specimen bottles before taking to the laboratory for identification and preservation, the soil samples were analyzed for moisture content, organic matter, phosphorus, nitrogen and potassium. Analysis of variance (ANOVA) was used to test for statistical difference between the mean of the physical parameters of the soil and arthropods of the sites; Duncan’s Multiple comparison of mean so as to measure similarities of the sampling stations. A total of 986 occurrence of arthropods were collected in Pwadzu dumpsite, A total of 15 arthropods species belonging to 14 families of 11 arthropod orders namely: Diptera, Coleoptera, Hymenoptera, Isopoda, Dictyoptera, Orthoptera, Spiropolida, Ixolida, Araneomorpha, Scorpionida and Lepidoptera, Meanwhile, the percentage value of the soil samples are: nitrogen (0.69), available phosphorus (130.83), Calcium (0.11), Potassium (4.55) respectively. The percentage of organic carbon was 2.39, percentage organic matter 4.13 and the percentage moisture is 12.41. The month of November indicated high value of Shannon-Wiener index (H1 = 1.821) which suggested this habitat of dumpsite had high diversity at that month than the October and December months period with values of 1.742 and 1.649 respectively. It indicated that there were high arthropod species diversity and abundance in Pwadzu suggests that there are relatively few successful species in this habitat in October and November. This study recommends that more studies should be done in order to establish the abundance and different types of arthropods inhabiting Pwadzu dumpsites.